Central Sleep Apnea on Commencement of Continuous Positive Airway Pressure in Patients With a Primary Diagnosis of Obstructive Sleep Apnea-Hypopnea - Lehman, Sanaz (American Academy of Sleep Medicine, 2007)
INTRODUCTION: Central sleep apnea (CSA) may occur in patients with snoring and obstructive sleep apnea-hypopnea (OSAH) during commencement of continuous positive airway pressure (CPAP) therapy. The presence of CSA may limit the effectiveness of CPAP therapy. The aims of this study were to assess the prevalence of CSA amongst patients starting CPAP for OSAH and to identify possible predictors of this condition. METHODS: We reviewed the polysomnograms (PSGs) and clinical records of 99 consecutive patients with a primary diagnosis of OSAH who were referred for an in-laboratory CPAP titration study. Patients with a CSA Index of ≥5 per hour at or near (±1 cm H(2)O) prescribed CPAP level formed the CSA-CPAP group. The remaining patients made up the noCSA-CPAP group. Demographic, baseline and CPAP titration PSG variables were compared between the 2 two groups. RESULTS: 13 subjects (13.1%) had CSA-CPAP. Patients with and without CSA-CPAP did not differ with respect to age or body mass index. 46% of patients with CSA-CPAP had CSA on their baseline PSGs compared with 8% in the noCSA-CPAP group (p <0.01). CSA-CPAP patients also had a higher apnea-hypopnea index (72.1 vs. 52.7 p = 0.02), a higher arousal index (43.3 vs. 29.2 p <0.01), and a higher mixed apnea index (6.8 vs. 1.3 p = 0.03), on their baseline PSGs. Therapeutic CPAP could not be determined in 2 CSA-CPAP patients due to a very high frequency (of severe) central apneas. In the remaining 11, the CPAP prescription to eliminate obstructive events was higher than in the noCSA-CPAP group (11.0 vs. 9.3 p = 0.08). AHI was greater both at or near prescribed CPAP (48.8 vs. 6.7 p <0.01) and overall (47.4 vs. 14.9 p <0.01). A history of ischemic heart disease or heart failure was more frequent amongst patients with CSA-CPAP than those without (p = 0.03). CONCLUSION: A significant minority of patients with a primary diagnosis of OSAH have either emergence or persistence of CSA on CPAP. Risk factors include male sex, history of cardiac disease, and CSA on baseline PSG. CITATION: Lehman S; Antic NA; Thompson C; Catcheside PG; Mercer J; McEvoy RD. Central sleep apnea on commencement of continuous positive airway pressure in patients with a primary diagnosis of obstructive sleep apnea-hypopnea. J Clin Sleep Med 2007;3(5):462-466.